Coffee, tea, and cocoa : market prospects and development lending - Singh, Shamsher; Singh, Shamsher; World Bank. (Baltimore : Published for the World Bank [by] Johns Hopkins University Press, 1977)
This paper consists of the markets for coffee, cocoa, and tea prepared for the use of World Bank staff. The Bank's commodity studies serve a dual purpose: to evaluate prospects for the export earnings of borrowing member countries and to assess the market prospects for individual commodities.
Includes bibliographical references.
usc 22/01/2019
Loans
Keywords: Coffee industry and trade; Cocoa industry and trade; Tea industry and trade; Economic assistance